In lands of foreign currency credit, bank lending channels run through? - Steven Ongena; Ibolya Schindele; Dzsamila Vonnák (Magyar Nemzeti Bank, 2017)
We study the impact of monetary policy on the supply of bank credit when bank lending is also denominated in foreign currencies. Accessing a comprehensive supervisory dataset from Hungary, we find that the supply of bank credit in a foreign currency is less sensitive to changes in domestic monetary conditions than the equivalent supply in the domestic currency. Changes in foreign monetary conditions similarly affect bank lending more in the foreign than in the domestic currency. Hence when banks lend in multiple currencies the domestic bank lending channel is weakened and international bank lending channels become operational.
Keywords: E51; F3; G21; 330; Bank balance-sheet channel; monetary policy; foreign currency lending